Sustainable tourism development: a case study of North Cyprus - Altınay, Mehmet; Hussain, Kashif (International Journal of Contemporary Hospitality Management / Emerald, 2005)
Purpose – The aim of this study is to find out the perceptions of tourism experts on environmental impacts of accommodation investments in Bafra, Karpaz region. Design/methodology/approach – Environmental impact assessment model is used to find out the impacts and a structured questionnaire is applied to tourism industry experts: top administrators of the concerned public offices, the representatives of related nongovernmental organizations, and the local administrators working in North Cyprus at various organizations. Findings – The preliminary findings of this research indicate that the most likely environmental impact of tourism is related with waste disposal, garbage treatment facilities and waste discharge by ships passing through the sea. Research limitations/implications – The present study is primarily focused on the virgin part of North Cyprus in which investors are most interested. Originality/value – This study serve as a guide for the state for policy planning and can serve as a guide to the construction industry because the government is interested in putting limitations on investments in the area to preserve the land, which would also provide guidelines for investors to follow before presenting an investment plan to the state
Keywords: Cyprus; Sustainable Development; Tourism